Intellectual and adaptive functioning in Sturge-Weber Syndrome. Issue 6 (17th August 2016) - Kavanaugh, Brian; Sreenivasan, Aditya; Bachur, Catherine; Papazoglou, Aimilia; Comi, Anne; Zabel, T. Andrew
Abstract : The present study examined the intellectual and adaptive functioning in a sample of children and young adults with Sturge-Weber Syndrome (SWS). A total of 80 research participants from a SWS study database underwent full neurological evaluation as part of their participation or concurrent medical care. Twenty-nine of the participants received neuropsychological evaluations. Analyses indicated no significant demographic or neurological differences between those who did and did not receive neuropsychological evaluations. Overall, the neuropsychological evaluation sample displayed significantly lower functioning relative to published normative data across domains of intellectual and adaptive functioning. Thirty-two percent of the sample displayed impaired performance (standard score ≤ 75) in intellectual functioning and 58% displayed impaired performance in adaptive functioning. Hemiparesis status independently predicted overall adaptive functioning while seizure frequency independently predicted overall intellectual functioning. Younger participants displayed significantly higher (more intact) ratings in adaptive functioning compared to older participants, specifically in overall adaptive functioning, motor skills, and community living skills. A composite measure of neurological status (SWS-NRS) incorporating seizure and hemiparesis status effectively distinguished between individuals with impaired or nonimpaired adaptive and intellectual functioning and showed promise as a screening method for identifying individuals with more involved intellectual and/or adaptive needs.